Effect of mental toughness on sporting performance: review of studies - Guszkowska, M.; Wojcik, K. (Baltic Journal of Health and Physical Activity, 2021)
The aim of the present review was to establish the correlation between mental toughness and sporting performance based on the results of studies published in scientific journals between 2000 and 2020. The keywords mental toughness and performance/outcomes/results/ competition were used to identify the papers. The search included the EBSCO and PubMed databases. Eventually, the analysis covered 18 articles. The research results presented in 16 papers confirmed the positive correlations of mental toughness with sport results and performance level. No such relationship was found only in equestrian and Alpine skiing athletes. Although mental toughness in basketball players did not correlate with the sport results, it was an important predictor. Higher mental toughness was found in athletes with better sports results, and it was a positive correlate or predictor of sports results. The relationships between mental toughness and competitive experience or age were not statistically significant. Various research tools were used to measure mental toughness: PPI, PPI-A, SMTQ, MTQ48, MTI, SMTI, MeBTough. The results confirm the positive correlation between mental toughness and sport results or performance levels in different sports, regardless of gender, age or level of sports skills. It seems appropriate to continue research on mental toughness in sport, including the relationship between mental toughness and sporting performance, differences between men and women, players in individual and team sports, the relationship between mental toughness and training experience, the athletes` age, and the effectiveness of mental toughness programs.